1998
DOI: 10.1006/viro.1998.9241
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Permissive Infection of Insect (Gypsy Moth) LD-652 Cells by Vaccinia Virus

Abstract: The members of Poxviridae family are among the most complex of animal viruses and subfamily members infect both vertebrate (Chordopoxvirinae) and invertebrate (Entomopoxvirinae) hosts, respectively. Vaccinia virus (VV) is the most commonly studied vertebrate virus and the entomopoxvirus of Amsacta moorei (AmEPV) is the prototypic insect virus. AmEPV, while not able to productively infect vertebrate cells, does enter vertebrate cells and expresses early genes after which the infection aborts although the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…This mode of transmission (termed circulative, nonpropagative mode) of geminiviruses thus appears to be in the intermediate mode between mechanical transmission and biological transmission. Some insect poxviruses (genus Entomopoxvirus) share with mammalian poxviruses similar cell entry and uncoating mechanisms as well as biochemical strategy for replication, the major difference being that the former viruses are defective in late gene expression in vertebrate cells, while the latter are defective in proteolytic processing of late viral proteins in insect cells (180,181). Polydnaviruses are obligate, symbiotic, double-stranded DNA viruses that infect insects.…”
Section: Few Dna Arbovirusesmentioning
confidence: 99%
“…This mode of transmission (termed circulative, nonpropagative mode) of geminiviruses thus appears to be in the intermediate mode between mechanical transmission and biological transmission. Some insect poxviruses (genus Entomopoxvirus) share with mammalian poxviruses similar cell entry and uncoating mechanisms as well as biochemical strategy for replication, the major difference being that the former viruses are defective in late gene expression in vertebrate cells, while the latter are defective in proteolytic processing of late viral proteins in insect cells (180,181). Polydnaviruses are obligate, symbiotic, double-stranded DNA viruses that infect insects.…”
Section: Few Dna Arbovirusesmentioning
confidence: 99%
“…The vaccinia viral vector and reporter gene used appeared to have no overt effect on the health of the insect or wing color pattern formation, an important property if vaccinia virus is to be used to express genes thought to be involved in this process. In addition, the fact that vaccinia virus, which is a vertebrate poxvirus, has the ability to infect butterflies in vivo as well as gypsy moth cells in vitro (9), suggests that vaccinia virus will also be a useful gene expression tool in other arthropod species for which classical genetic methods are either impractical or unavailable.…”
mentioning
confidence: 99%
“…It has been reported that vaccinia virus, a vertebrate poxvirus, is able to infect gypsy moth cell lines in vitro (9). The vaccinia virus enters the gypsy moth cells and carries out both early and late viral protein synthesis as well as viral DNA replication (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations